Preparation method of composite material, composite material, photoelectric device and display device

Through the ZNO/MXENE composite material prepared by water heat and microwave treatment, the composite material that forms inorganic semiconductor particles and MXENE quantum dots through electrostatic adsorption to solve the problem of poor stability of composite materials in existing technologies, and improves the luminous performance of optical components and the light electrical device. life.

CN119370846APending Publication Date: 2025-01-28TCL TECHNOLOGY GROUP CORPORATION +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310939099.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The ZnO/Mxene composite materials prepared by the prior art have poor stability, which affects the efficiency and life of optoelectronic devices.

Method used

Methods of water heat treatment and microwave treatment are used to prepare composite materials, and a composite material for inorganic semiconductor particles and MXENE quantum dots can be formed through the static adsorption effects between MXENE and inorganic semiconductor particles.

Benefits of technology

Improve the stability of the electric field stability between the inorganic semiconductor particles and the MXNE quantum dot, and enhance the luminous performance and life of the optoelectric component.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370846A_ABST
    Figure CN119370846A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite material, the composite material, a photoelectric device and a display device. The preparation method of the composite material comprises the following steps: providing a precursor solution, wherein the precursor solution comprises Mxene, a metal cation source and a first solvent; carrying out hydrothermal treatment to obtain an inorganic semiconductor particle / Mxene composite material solution; the inorganic semiconductor particle / Mxene composite material solution is subjected to microwave treatment, the composite material is obtained, and the composite material comprises inorganic semiconductor particles and Mxene quantum dots. According to the preparation method of the composite material, the inorganic semiconductor particles and the Mxene quantum dots have relatively strong electric field stability, so that the photoelectric device comprising the inorganic semiconductor particles and the Mxene quantum dots has relatively good luminescence performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optoelectronic devices, and in particular to a method for preparing a composite material, a composite material, an optoelectronic device and a display device. Background Art

[0002] Currently, the widely used optoelectronic devices are organic light-emitting devices (OLED) and quantum dot light-emitting devices (QLED). OLED has become the mainstream technology in the field of display technology due to its excellent display performance such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLED has the advantages of saturated color of emitted light, adjustable wavelength, low start-up voltage, good solution processability, easy fine control of quantum dots, and high quantum yield of photoluminescence and electroluminescence. In recent years, it has become a strong competitor of OLED.

[0003] The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the optoelectronic device and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules and finally producing visible light.

[0004] ZnO / Mxene composites are used in the electron transport layer due to their good electron transport properties.

[0005] However, the stability of the ZnO / Mxene composite material prepared by the existing technology is poor and needs to be further improved. Summary of the invention

[0006] In a first aspect, the present application provides a method for preparing a composite material, comprising the following steps:

[0007] Providing a precursor solution, wherein the precursor solution includes Mxene, a metal cation source and a first solvent;

[0008] Hydrothermal treatment to obtain an inorganic semiconductor particle / Mxene composite material solution;

[0009] The inorganic semiconductor particle / Mxene composite material solution is subjected to microwave treatment to obtain a composite material, wherein the composite material comprises inorganic semiconductor particles and Mxene quantum dots.

[0010] In a second aspect, the present application also provides a composite material, comprising inorganic semiconductor particles and Mxene quantum dots, wherein the inorganic semiconductor particles are doped in the Mxene quantum dots.

[0011] In a third aspect, the present application further provides a photoelectric device, comprising a first electrode and a second electrode arranged opposite to each other, and also comprising an electron transport layer located between the first electrode and the second electrode, wherein the material of the electron transport layer comprises the above-mentioned composite material.

[0012] In a fourth aspect, the present application also provides a display device, comprising the above-mentioned optoelectronic device.

[0013] The preparation method of the composite material described in the present application can make the inorganic semiconductor particles and the Mxene quantum dots have a strong electric field stability, thereby making the optoelectronic device containing the composite material have a better luminescence performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0015] Figure 1 is a flow chart of a method for preparing a composite material provided in an embodiment of the present application;

[0016] Figure 2 is a schematic structural diagram of an optoelectronic device provided in an embodiment of the present application;

[0017] Figure 3 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0018] Figure 4 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0019] Figure 5 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0020] Figure 6 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0021] Figure 7 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0022] Figure 8 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;

[0023] Fig. 9 It is a flow chart of a method for preparing a photoelectric device provided in an embodiment of the present application.

[0024] Reference numerals:

[0025] Optoelectronic device 100 ; first electrode 10 ; electron transport layer 20 ; second electrode 30 ; light emitting layer 40 ; hole transport layer 50 ; hole injection layer 60 . DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0027] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0028] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0029] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0030] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0032] N-type inorganic semiconductor particles are considered to be one of the most popular materials for preparing electron transport layers of high-efficiency optoelectronic devices due to their high electron mobility and hole blocking properties. However, N-type inorganic semiconductor particles prepared by the prior art (e.g., N-type inorganic semiconductor particles prepared at room temperature) are usually easy to agglomerate at room temperature, and will experience positive aging under the action of electric field and / or temperature, resulting in the attenuation of the efficiency and life of optoelectronic devices.

[0033] The technical solution of this application is as follows:

[0034] First, see Figure 1 The present invention provides a method for preparing a composite material, comprising the following steps:

[0035] Step S11, providing a precursor solution, wherein the precursor solution includes Mxene, a metal cation source and a first solvent;

[0036] Step S12, hydrothermal treatment, so that Mxene and the metal cation source react, grow inorganic semiconductor particles on the surface of the Mxene sheet structure, form an inorganic semiconductor particle / Mxene composite material, and obtain an inorganic semiconductor particle / Mxene composite material solution, wherein the inorganic semiconductor particle / Mxene composite material includes Mxene nanosheets and inorganic semiconductor particles loaded on the surface of the Mxene nanosheets;

[0037] Step S13, subjecting the inorganic semiconductor particle / Mxene composite material solution to microwave treatment to cause the Mxene nanosheets to break into Mxene quantum dots centered on the inorganic semiconductor particles loaded on the surface of the Mxene nanosheets, thereby obtaining a composite material.

[0038] The composite material includes inorganic semiconductor particles and Mxene quantum dots. The inorganic semiconductor particles are doped in the Mxene quantum dots. The inorganic semiconductor particles are attached to the Mxene quantum dots through electrostatic adsorption. In other words, the inorganic semiconductor particles and the Mxene quantum dots are combined through electrostatic adsorption.

[0039] For the preparation method of the composite material described in this application, first, an inorganic semiconductor particle / Mxene composite material solution is prepared, and then it is subjected to microwave treatment. Since Mxene is a two-dimensional inorganic compound with a nano-sheet structure, microwave treatment can break Mxene nanosheets into Mxene quantum dots with the inorganic semiconductor particles loaded on their surfaces as the center, thereby obtaining quantum effects, making the prepared composite material have high electron transport performance. In addition, there is a strong binding force between the inorganic semiconductor particles and the Mxene quantum dots, making the composite material have good electric field stability and thus a long lifespan.

[0040] In the step S11:

[0041] The chemical general formula of the Mxene is M n+1 X n T x , where M is selected from transition metal elements, and the transition metal elements can be selected from one or more of any transition metal elements known in the art. For example, they can be selected from, but not limited to, one or more of Ti, Nb, V, Mo, Zr, Hf, Ta, Cr, Sc; X is selected from one or more of C and N; T x is a surface active functional group, including one or more of -OH, -O, -F, -Cl, -Br, where 0 < x ≤ 2; n is any integer among 1, 2, and 3.

[0042] As an example, in some embodiments, the Mxene includes, but is not limited to, Ti 3 C 2 T x 、Ti 2 CT x 、TiNbCT x 、Ti 3 CNT x 、Ta 4 C 3 T x 、Nb 2 CT x 、Nb 4 C 3 T x 、V 2 CT x 、Mo 2 CTx and Ti 4 N 3 T x One or more of, where 0 <x≤2。

[0043] The metal cation source includes, but is not limited to, one or more of a zinc source, a titanium source, a tin source, a zirconium source, and a tantalum source.

[0044] The zinc source includes, but is not limited to, one or more of zinc acetate, zinc sulfate, zinc nitrate, and zinc chloride.

[0045] The titanium source includes, but is not limited to, one or more of titanium acetate, titanium sulfate, titanium nitrate, and titanium chloride.

[0046] The tin source includes, but is not limited to, one or more of tin acetate, tin sulfate, tin nitrate, and tin chloride.

[0047] The zirconium source includes, but is not limited to, one or more of zirconium acetate, zirconium sulfate, zirconium nitrate, and zirconium chloride.

[0048] The tantalum source includes, but is not limited to, one or more of tantalum acetate, tantalum sulfate, tantalum nitrate, and tantalum chloride.

[0049] In some embodiments, a doping element source is further added to the precursor solution, so that the prepared inorganic semiconductor particles can be doped with the doping element, which is beneficial to improving the stability of the inorganic semiconductor particles.

[0050] The doping element source includes, but is not limited to, one or more of magnesium salts, lithium salts, manganese salts, yttrium salts, lanthanum salts, copper salts, nickel salts, zirconium salts, cerium salts, indium salts, gallium salts, and tin salts. It is understandable that the doping element provided by the doping element source is different from the type of the metal element in the metal cation source.

[0051] The magnesium salt may include, but is not limited to, one or more of magnesium acetate, magnesium nitrate, magnesium chloride, magnesium bromide, magnesium sulfate, and magnesium acetylacetonate.

[0052] The lithium salt may include, but is not limited to, one or more of lithium acetate, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, and lithium acetylacetonate.

[0053] The manganese salt may include, but is not limited to, one or more of manganese acetate, manganese nitrate, manganese chloride, manganese bromide, manganese sulfate, and manganese acetylacetonate.

[0054] The yttrium salt may include, but is not limited to, one or more of yttrium acetate, yttrium nitrate, yttrium chloride, yttrium bromide, yttrium sulfate, and yttrium acetylacetonate.

[0055] The lanthanum salt may include, but is not limited to, one or more of lanthanum acetate, lanthanum nitrate, lanthanum chloride, lanthanum bromide, lanthanum sulfate, and lanthanum acetylacetonate.

[0056] The copper salt may include, but is not limited to, one or more of copper acetate, copper nitrate, copper chloride, copper bromide, copper sulfate, and copper acetylacetonate.

[0057] The nickel salt may include, but is not limited to, one or more of nickel acetate, nickel nitrate, nickel chloride, nickel bromide, nickel sulfate, and nickel acetylacetonate.

[0058] The zirconium salt may include, but is not limited to, one or more of zirconium acetate, zirconium nitrate, zirconium chloride, zirconium bromide, zirconium sulfate, and zirconium acetylacetonate.

[0059] The cerium salt may include, but is not limited to, one or more of cerium acetate, cerium nitrate, cerium chloride, cerium bromide, cerium sulfate, and cerium acetylacetonate.

[0060] The indium salt may include, but is not limited to, one or more of indium acetate, indium nitrate, indium chloride, indium bromide, indium sulfate, and indium acetylacetonate.

[0061] The gallium salt may include, but is not limited to, one or more of gallium acetate, gallium nitrate, gallium chloride, gallium bromide, gallium sulfate, and gallium acetylacetonate.

[0062] The tin salt may include, but is not limited to, one or more of tin acetate, tin nitrate, tin chloride, tin bromide, tin sulfate, and tin acetylacetonate.

[0063] The molar ratio of the doping element source to the metal cation source is greater than 0 and less than or equal to 0.3:1, for example, 0.5:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, etc. Within the ratio range, the prepared composite material is advantageously provided with good electron transport performance and stability.

[0064] The first solvent includes but is not limited to an alcohol solvent, and the alcohol solvent includes but is not limited to one or more of ethylene glycol, diethylene glycol, 2-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.

[0065] In the precursor solution, the concentration range of the Mxene is 0.6-1 mg / mL, for example, 0.6 mg / mL, 0.65 mg / mL, 0.7 mg / mL, 0.75 mg / mL, 0.8 mg / mL, 0.85 mg / mL, 0.9 mg / mL, 0.95 mg / mL, 1 mg / mL, etc.; the concentration range of the metal cation source is 0.01-0.1 mmol / mL, for example, 0.01 mmol / mL, 0.02 mmol / mL, 0.03 mmol / mL, 0.04 mmol / mL, 0.05 mmol / mL, 0.06 mmol / mL, 0.07 mmol / mL, 0.08 mmol / mL, 0.09 mmol / mL, 0.1 mmol / mL, etc. Within the above concentration range of Mxene and the metal cation source, it is beneficial for the prepared composite material to have good electronic transport performance and stability.

[0066] In a first embodiment, the method for preparing the precursor solution includes:

[0067] A, dissolving a metal cation source in a second solvent to obtain a metal cation source solution; and

[0068] B. Mixing the metal cation source solution with the Mxene colloid solution to obtain a precursor solution.

[0069] The second solvent is selected from one or more of the alcohol solvents mentioned above.

[0070] The solvent in the Mxene colloid solution includes water and one or more of the alcohol solvents mentioned above.

[0071] In at least one embodiment, the solvent in the Mxene colloidal solution is a mixed solvent of water and an alcohol solvent. Further, in the mixed solvent of water and an alcohol solvent, the molar ratio of water to the alcohol solvent is (10-50):1, for example, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, etc. Within the range of the molar ratio, it is beneficial to fully and evenly disperse the Mxene, and it is beneficial for the prepared composite material to have better electronic transport performance and stability and other properties.

[0072] The method of mixing the metal cation source solution with the Mxene colloidal solution is to vigorously stir for 1 to 3 hours at 20 to 30° C. This is conducive to fully and evenly mixing the metal cation source and Mxene, thereby making the prepared composite material have better electronic transport performance and stability.

[0073] In some second embodiments, the method for preparing the precursor solution includes:

[0074] The Mxene, the metal cation source and the solvent are directly mixed in proportion to obtain a precursor solution.

[0075] The Mxene can be prepared by a known preparation method. As an example, in at least some embodiments, Ti 3 C 2 T x For example, the Mxene is prepared by the following method:

[0076] a. Commercial Ti 2 AlC and TiC powders were mixed in a molar ratio of 1:1, ball milled for 18 h, and then sintered at 1350 °C for 2 h under Ar flow protection to obtain bulk TiC. 3 AlC 2 , crushed and sieved to obtain Ti with a particle size of 38 μm 3 AlC 2 powder;

[0077] b. Add 1 g Ti to a LiF-HCl solution (containing 0.67 g LiF, 6 M HCl concentration, and 10 mL solution volume). 3 AlC 2 The powder was stirred for 30 min, stirred at 35 ° C for 24 h, washed with ethanol, centrifuged at 3500 rpm for 5 min, and this process was repeated several times until the pH value of the supernatant reached 6, then ultrasonic bathed under Ar bubbling for 1 h, centrifuged at 3500 rpm for 1 h, and the supernatant was collected to obtain Ti end-capped with -O, -OH, -Cl and -F. 3 C 2 T x .

[0078] In step S12:

[0079] The temperature of the hydrothermal treatment is 170-200°C, and the time is 30min-1h. Within the temperature and time range, it is conducive to the generation of nanoscale inorganic semiconductor particles on the surface of Mxene. As an example, the temperature of the hydrothermal treatment can be 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, etc., and the time of the hydrothermal treatment can be 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc.

[0080] In some embodiments, the hydrothermal treatment is performed in a stainless steel autoclave lined with polytetrafluoroethylene.

[0081] In some embodiments, after the hydrothermal treatment and before obtaining the inorganic semiconductor particle / Mxene composite material solution, it also includes: adding a precipitant to the reaction system to precipitate the inorganic semiconductor particle / Mxene composite material and separate it from the solvent, extracting the precipitate, and then dispersing the precipitate in a dispersant.

[0082] The precipitant may include, but is not limited to, one or more of ethyl acetate, n-octane, n-hexane, and n-heptane.

[0083] The dispersant may be one or more of the alcohol solvents mentioned above.

[0084] In some embodiments, in the inorganic semiconductor particle / Mxene composite material solution, the concentration of the inorganic semiconductor particle / Mxene composite material is 20 to 100 mg / ml, for example, 20 mg / ml, 25 mg / ml, 30 mg / ml, 35 mg / ml, 40 mg / ml, 45 mg / ml, 50 mg / ml, 55 mg / ml, 60 mg / ml, 65 mg / ml, 70 mg / ml, 75 mg / ml, 80 mg / ml, 85 mg / ml, 90 mg / ml, 95 mg / ml, 100 mg / ml, etc. Within the concentration range, it is beneficial for the inorganic semiconductor particle / Mxene composite material to be fully and uniformly dispersed, and it is also beneficial for preparing a composite material with good electron transport performance and stability.

[0085] In step S13:

[0086] The power of the microwave treatment is 550-570W, for example, 550W, 552W, 554W, 555W, 556W, 558W, 560W, 562W, 564W, 565W, 566W, 568W, 570W, etc., and the time is 3-5min, for example, 3min, 3.5min, 4min, 4.5min, 5min, etc. Within the power and time range, it is beneficial to make the size of the prepared Mxene quantum dot material uniform and the dispersion is good.

[0087] In some embodiments, after subjecting the inorganic semiconductor particle / Mxene composite material solution to microwave treatment, the process further comprises: filtering to remove the solvent to obtain the composite material.

[0088] The filtration can be performed using a known nanoparticle filtration method. In at least some embodiments, the filtration is performed using a needle filter membrane.

[0089] In a second aspect, an embodiment of the present application further provides a composite material prepared by the above-mentioned preparation method, wherein the composite material comprises inorganic semiconductor particles and Mxene quantum dots, wherein the inorganic semiconductor particles are doped in the Mxene quantum dots.

[0090] In at least one embodiment, the inorganic semiconductor particles are attached to the surface of the Mxene quantum dots by electrostatic adsorption.

[0091] The surface active functional groups T in the Mxene quantum dots x The metal cations in the inorganic semiconductor particles can react with the negatively charged surface active functional groups T x Electrostatic adsorption occurs between the Mxene quantum dots, causing the inorganic semiconductor particles to adhere to the surface of the Mxene quantum dots. In addition, there is a quantum effect between the Mxene quantum dots and the inorganic semiconductor particles, which can effectively enhance the binding force between the two.

[0092] The inorganic semiconductor particles include but are not limited to one or more of doped metal oxide particles and undoped metal oxide particles, wherein the metal oxide in the doped metal oxide and the metal oxide in the undoped metal oxide particles independently include ZnO, TiO 2 SnO 2 、ZrO 2 、 2 O 5 The doping elements in the doped metal oxide include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn.

[0093] It can be understood that the inorganic semiconductor particles can be single inorganic semiconductor particles or agglomerates of inorganic semiconductor particles.

[0094] In some embodiments, the average particle size of the inorganic semiconductor particles is 50 to 200 nm, for example, 50 nm, 60 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm. Within the particle size range, the inorganic semiconductor particles can be effectively adsorbed on the Mxene quantum dots, effectively inhibit the charge localization of the surface active groups of the Mxene quantum dots, and effectively adjust the energy band structure of the Mxene quantum dots. In the composite material, the mass ratio of the inorganic semiconductor particles to the Mxene quantum dots ranges from 30% to 60%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc. Within the ratio range, both the work function of the Mxene quantum dots can be effectively adjusted and the surface charge localization of the Mxene quantum dots can be effectively inhibited.

[0095] Mxene quantum dots have excellent metallic conductivity, adjustable work function and abundant surface active groups, among which the surface active groups of Mxene quantum dots are prone to graphene-like charge localization, which is not conducive to the transmission of electrons. In the composite material described in the present application, the metal ions in the inorganic semiconductor particles can produce electrostatic adsorption between the surface active groups of the Mxene quantum dots, thereby effectively inhibiting the charge localization of the surface active groups of the Mxene quantum dots, realizing the surface charge delocalization of the Mxene quantum dots, and effectively improving the electron transmission capacity of the Mxene quantum dots. In addition, there is a strong binding ability between the inorganic semiconductor particles and the Mxene quantum dots, which makes the composite material have strong stability.

[0096] Third, see Figure 2 An embodiment of the present application provides an optoelectronic device 100, comprising a first electrode 10, an electron transport layer 20, and a second electrode 30 stacked in sequence, wherein the material of the electron transport layer 20 includes the composite material.

[0097] See also Figures 3-4 In some embodiments, the optoelectronic device 100 further includes a light-emitting layer 40 , and the light-emitting layer 40 is located between the first electrode 10 and the electron transport layer 20 , or between the second electrode 30 and the electron transport layer 20 .

[0098] The material of the electron transport layer of the optoelectronic device 100 described in the present application is the composite material. The composite material has good electron transport performance and stability, and can effectively improve the efficiency and life of the optoelectronic device 100.

[0099] See also Figures 5-6In some embodiments, the optoelectronic device 100 further includes a hole transport layer 50 , and the hole transport layer 50 is located on a side of the light emitting layer 40 away from the electron transport layer 20 .

[0100] See also Figures 7-8 In some embodiments, the optoelectronic device 100 further includes a hole injection layer 60 , and the hole injection layer 60 is located on a side of the hole transport layer 50 away from the light-emitting layer 40 .

[0101] The first electrode 10 and the second electrode 30 are electrodes for optoelectronic devices known in the art, for example, they can independently include but are not limited to doped metal oxide electrodes, composite electrodes, graphene electrodes, carbon nanotube electrodes, metal single substance electrodes or alloy electrodes. The material of the doped metal oxide electrode can include but is not limited to one or more of indium doped tin oxide (ITO), fluorine doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), gallium doped zinc oxide (GZO), indium doped zinc oxide (IZO), magnesium doped zinc oxide (MZO), aluminum doped magnesium oxide (AMO), and cadmium doped zinc oxide. The composite electrode is an electrode formed by stacking two or more layers of conductive materials, such as AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF 2 / Al、CsF / Al、CaCO 3 / Al、BaF 2 / Ca / Al, etc., where " / " represents a stacked structure, for example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence. The material of the metal single substance electrode may include but is not limited to one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba. The alloy electrode includes but is not limited to Au:Mg alloy electrode and Ag:Mg alloy electrode.

[0102] In some embodiments, the electrode far from the electron transport layer 20 in the first electrode 10 and the second electrode 30 is an electrode with a relatively high work function, for example, it may include but is not limited to a doped metal oxide electrode with a relatively high work function, a metal single substance electrode with a relatively high work function, and a carbon nanotube electrode. The metal single substance electrode with a relatively high work function may be selected from but is not limited to Ni, Pt, Au, Ag, Ir, etc.

[0103] In some embodiments, the electrode near the electron transport layer 20 in the first electrode 10 and the second electrode 30 is an electrode with a relatively low work function, for example, it may include but is not limited to a metal single substance electrode with a relatively low work function, a composite electrode with a relatively low work function, and an alloy electrode with a relatively low work function. The metal single substance electrode with a relatively low work function may be Ca, Ba, Al, Mg, etc. The composite electrode with a relatively low work function may be Ca / Al, LiF / Ca, LiF / Al, BaF 2 / Al、CsF / Al、CaCO 3 / Al、BaF 2 / Ca / Al, etc. The alloy electrodes with relatively low work functions are Au:Mg and Ag:Mg, etc.

[0104] The material of the light-emitting layer 40 may include, but is not limited to, one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0105] The organic light emitting material may include but is not limited to CBP:Ir(mppy) 3 (4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)), TCTX:Ir(mmpy)(4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing BN covalent bonds, HLCT (hybridized localized charge transfer excited state) materials, Exciplex (exciplex) luminescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives. One or more thereof.

[0106] The quantum dot light-emitting material may include, but is not limited to, one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.

[0107] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots may respectively include but are not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds may include, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds may include, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may include but is not limited to one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The I-III-VI group compound may include but is not limited to CuInS 2 、CuInSe 2 AgInS 2 One or more of .

[0108] As an example, the core-shell structured quantum dots may include, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0109] The perovskite semiconductor material may include but is not limited to doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has the general structural formula AMX 3 , where A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX 3 , where B is an organic amine cation, including CH 3 (CH 2 ) n-2 NH 3 + or [NH 3 (CH 2 ) n NH 3 ] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .

[0110] The material of the hole transport layer 50 may also be a material known in the art for a hole transport layer, for example, may be selected from but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazolyl) azole) (PVK) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine (NPB), spiro NPB, poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-bis(4-methylphenyl)aniline](TAPC), 1,3-bis(carbazole-9-yl)benzene(MCP), polyaniline, polypyrrole, poly(p-phenylene vinylene), aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO 3 , doped or undoped WO3 , doped or undoped V 2 O 5 , doped or undoped P-type GaN, doped or undoped CrO 3 , doped or undoped CuO or more.

[0111] The material of the hole injection layer 60 may also be a material known in the art for a hole injection layer, for example, may be selected from but not limited to 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO 3 Derivatives (PEDOT:PSS:s-MoO 3 ), one or more of 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0112] The thickness of the first electrode 10 and the second electrode 30 are independently 40 to 80 nm.

[0113] The thickness of the electron transport layer 20 is 40-60 nm.

[0114] The thickness of the light emitting layer 40 is 30-60 nm.

[0115] The thickness of the hole transport layer 50 is 20-60 nm.

[0116] The hole injection layer 60 has a thickness of 20-60 nm.

[0117] It is understandable that the optoelectronic device 100 may also be provided with some functional layers conventionally used in optoelectronic devices to help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, etc.

[0118] It can be understood that the materials of each layer of the optoelectronic device 100 can be adjusted according to the light emitting requirements of the optoelectronic device 100 .

[0119] In some embodiments, the optoelectronic device 100 further includes a substrate, and the substrate is disposed on a side of the first electrode 10 away from the light-emitting layer 40 , or the substrate is disposed on a side of the second electrode 30 away from the light-emitting layer 40 .

[0120] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0121] It can be understood that the optoelectronic device 100 can be an upright optoelectronic device or an inverted optoelectronic device. The optoelectronic device 100 can be a quantum dot optoelectronic device (QLED) or an organic optoelectronic device (OLED).

[0122] The electron transport layer 20 of the optoelectronic device 100 includes black titanium dioxide, thereby having higher luminous efficiency and longer lifespan.

[0123] Fourth, please refer to Figure 2 and Fig. 9 The present application also provides a method for preparing a photoelectric device, comprising the following steps:

[0124] Step S21, providing a photoelectric device preform, wherein the photoelectric device preform includes a first electrode 10;

[0125] Step S22, providing the composite material, and disposing the composite material on the optoelectronic device preform to obtain an electron transport layer 20;

[0126] Step S23 , forming a second electrode 30 on the electron transport layer 20 to obtain a photoelectric device 100 .

[0127] See also Figure 3 In some embodiments, the optoelectronic device preform further includes a light-emitting layer 40 disposed on the first electrode 10 , and the composite material is disposed on the light-emitting layer 40 .

[0128] See also Figure 4 In some other embodiments, forming the second electrode 30 on the electron transport layer 20 includes: sequentially forming a stacked light-emitting layer 40 and the second electrode 30 on the electron transport layer 20 .

[0129] See also Figure 5 In some embodiments, the optoelectronic device preform further includes a hole transport layer 50 and a light-emitting layer 40 which are sequentially stacked on the first electrode 10 , and the composite material is disposed on the light-emitting layer 40 .

[0130] See also Figure 6 In some other embodiments, forming the second electrode 30 on the electron transport layer 20 includes: sequentially forming a stacked light-emitting layer 40, a hole transport layer 50 and a second electrode 30 on the electron transport layer 20.

[0131] See also Figure 7 In some embodiments, the optoelectronic device preform further includes a hole injection layer 60 , a hole transport layer 50 and a light-emitting layer 40 which are sequentially stacked on the first electrode 10 , and the composite material is disposed on the light-emitting layer 40 .

[0132] See also Figure 8 In other embodiments, forming the second electrode 30 on the electron transport layer 20 includes: sequentially forming a stacked light-emitting layer 40, a hole transport layer 50, a hole injection layer 60 and a second electrode 30 on the electron transport layer 20.

[0133] The method of forming the second electrode 30, the light-emitting layer 40, the hole transport layer 50, and the hole injection layer 60, as well as the method of setting the composite material on the optoelectronic device preform can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip pulling, immersion, spraying, rolling, casting, slit coating, and strip coating.

[0134] In at least some embodiments, the method of disposing the composite material on the optoelectronic device preform includes: dissolving the composite material in a third solvent to obtain a composite material dispersion, and spin coating the composite material dispersion on the optoelectronic device preform.

[0135] The third solvent includes but is not limited to alcohol solvents, and the alcohol solvents include but are not limited to one or more of methanol, ethanol, isopropanol, and ethylene glycol.

[0136] In some embodiments, in the composite material dispersion, the concentration of the composite material is 20-50 mg / mL. Within the concentration range, the composite material can be evenly dispersed in the solvent, which is conducive to preparing an electron transport layer 20 with good film-forming effect and suitable thickness.

[0137] In some embodiments, the step of spin coating the composite material dispersion on the optoelectronic device preform further includes annealing, which is conducive to preparing an electron transport layer 20 with good crystallinity and excellent performance.

[0138] The annealing temperature is 60-100° C. and the annealing time is 1-50 min. Within the temperature and time range, it is beneficial to prepare the electron transport layer 20 with a good film-forming effect.

[0139] It can be understood that when the optoelectronic device 100 also includes functional layers conventionally used in optoelectronic devices that help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, etc., the preparation method of the optoelectronic device 100 may also include the step of preparing the above-mentioned functional layers using conventional techniques in the field.

[0140] The method for preparing the optoelectronic device described in the present application can prepare an optoelectronic device 100 having good luminous efficiency and long life.

[0141] In a fifth aspect, the present application also relates to a display device, which includes the optoelectronic device 100 .

[0142] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0143] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0144] Example 1

[0145] ZnO / Ti 3 C 2 T x Composite material preparation:

[0146] 1) Commercial Ti 2 AlC and TiC powders were mixed in a molar ratio of 1:1, ball milled for 18 h, and then sintered at 1350 °C for 2 h under Ar flow protection to obtain bulk TiC. 3 AlC 2 , crushed and sieved to obtain Ti with a particle size of 38 μm 3 AlC 2 powder;

[0147] 2) Add 1gTi into the LiF-HCl solution (containing 0.67g LiF, HCl concentration is 6M, and the volume of the solution is 10mL). 3 AlC 2The powder was stirred for 30 min, stirred at 35 ° C for 24 h, washed with ethanol, centrifuged at 3500 rpm for 5 min, and this process was repeated several times until the pH value of the supernatant reached 6, then ultrasonic bathed under Ar bubbling for 1 h, centrifuged at 3500 rpm for 1 h, and the supernatant was collected to obtain Ti end-capped with -O, -OH, -Cl and -F. 3 C 2 T x ;

[0148] 3) Add 0.9 mmol of zinc acetate to a mixed solution of diethylene glycol and water to form a zinc salt solution with a total concentration of 0.03 M, and then add the mixed solution to 150 mL of Ti 3 C 2 T x In the colloidal solution (0.6 mg / ml), Ti 3 C 2 T x The solvent of the colloidal solution was a mixed solvent of water and diethylene glycol in a molar ratio of 10. The mixture was vigorously stirred at 25°C for 60 min, and the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and hydrothermally treated at 180°C for 1 h. The reaction solution was washed and precipitated with ethyl acetate and n-octane, respectively, to obtain ZnO / Ti 3 C 2 T x Composite material, then ZnO / Ti 3 C 2 T x The composite material was dispersed in ethanol to obtain ZnO / Ti 3 C 2 T x The composite material solution was subjected to microwave treatment at a power of 560 W for 4 min, and then filtered through a needle filter membrane to obtain ZnO / Ti 3 C 2 T x Quantum dot composites.

[0149] Photoelectric device preparation:

[0150] A glass substrate having an ITO first electrode 10 with a thickness of 50 nm is provided, the ITO conductive glass is cleaned with a detergent to preliminarily remove stains on the surface, and then ultrasonically cleaned in deionized water, isopropanol, acetone, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally dried with high-purity nitrogen;

[0151] In a glove box, spin-coat the TFB material on the first electrode 10 and anneal at 150° C. for 30 min to obtain a hole transport layer 50 with a thickness of 50 nm;

[0152] Spin-coat CdZnSe quantum dot material on the hole transport layer 50 and anneal at 80° C. for 30 min to obtain a light-emitting layer 40 with a thickness of 30 nm;

[0153] The ZnO / Ti 3 C 2 T x The composite material is dispersed in ethanol to obtain a dispersion liquid, the dispersion liquid is spin-coated on the light-emitting layer 40, and annealed at 80° C. for 10 minutes to obtain an electron transport layer 20 with a thickness of 40 nm;

[0154] Ag is evaporated on the electron transport layer 20 to obtain a cathode with a thickness of 50 nm;

[0155] The optoelectronic device 100 is obtained by packaging in an environment where both the oxygen content and the water content are lower than 0.1 ppm.

[0156] Example 2

[0157] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the molar ratio of water to diethylene glycol is 30.

[0158] Example 3

[0159] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the molar ratio of water to diethylene glycol is 50.

[0160] Example 4

[0161] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the microwave treatment time is 3 minutes.

[0162] Example 5

[0163] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the microwave treatment time is 5 min.

[0164] Example 6

[0165] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the microwave treatment time is 1 min.

[0166] Example 7

[0167] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the microwave treatment time is 10 min.

[0168] Example 8

[0169] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, 0.05 mmol of magnesium acetate is further added to the zinc salt solution.

[0170] Example 9

[0171] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, tin acetate is used to replace zinc acetate in Embodiment 1.

[0172] Comparative Example 1

[0173] This comparative example is substantially the same as Example 1, except that the material of the electron transport layer in this comparative example is ZnO particles.

[0174] Comparative Example 2

[0175] This comparative example is basically the same as Example 1, except that the material of the electron transport layer in this comparative example is ZnO@Ti 3 C 2 T x Composite material, the ZnO@Ti 3 C 2 T x ZnO and Ti in composite materials 3 C 2 T x The ratio of ZnO / Ti in Example 1 3 C 2 T x ZnO and Ti in Quantum Dot Composites 3 C 2 T x The ratio is the same, and in this embodiment, ZnO@Ti 3 C 2 T x The composite material is composed of ZnO particles and Ti 3 C 2 T x It is prepared by simple physical mixing in proportion.

[0176] Comparative Example 3

[0177] This comparative example is basically the same as Example 1, except that the material of the electron transport layer in this comparative example is ZnO / Ti in Example 1. 3 C 2 T x Composite materials.

[0178] The external quantum efficiency EQE and lifespan T95 tests were performed on the optoelectronic devices of Examples 1 to 9 and Comparative Examples 1 to 3. The test results are shown in Table 1.

[0179] The test method of external quantum efficiency EQE is as follows: using FPD optical property measurement equipment from Foster, controlling the efficiency test system built by QE PRO spectrometer, Keithley 2400, and Keithley 6485 through LabView, measuring parameters such as voltage, current, brightness, and luminescence spectrum, and calculating the device external quantum efficiency EQE;

[0180] The T95 test method for lifetime is: in CDA gas, under constant current or voltage drive, measure the time it takes for the device brightness to decay to a certain proportion of the maximum brightness. The time it takes for the brightness to decay to 95% of the maximum brightness is defined as T95, and this lifetime is the actual measured lifetime.

[0181] Table 1:

[0182]

[0183]

[0184] From Table 1 we can see that:

[0185] Compared with the optoelectronic device of Comparative Example 1, the optoelectronic devices of Examples 1 to 9 have higher luminous efficiency and longer life. It can be seen that the composite material prepared by the preparation method of the present application as an electron transport layer material can effectively improve the efficiency and life of the optoelectronic device. The reason may be that the composite material prepared by the preparation method of the present application has higher electron transport layer performance and better stability.

[0186] Compared with the optoelectronic devices of Comparative Examples 2 to 3, the optoelectronic device of Example 1 has higher luminous efficiency and longer life. It can be seen that the composite material prepared by the preparation method of the present application as an electron transport layer material can effectively improve the efficiency and life of the optoelectronic device. The reason may be that the composite material prepared by the preparation method of the present application has higher electron transport layer performance and better stability.

[0187] Compared with the optoelectronic devices of Examples 6 and 7, the optoelectronic devices of Examples 1 and 4 to 5 have higher luminous efficiency and longer life. The reason may be that the microwave treatment time is short when the composite material of Example 6 is prepared, resulting in uneven size of the formed Mxene (poor particle size uniformity), which in turn affects the electronic transmission performance and stability of the composite material; while the microwave treatment time is long when the composite material of Example 7 is prepared, which may cause the agglomeration of Mxene quantum dots or inorganic semiconductor particles, thereby affecting the electronic transmission performance and stability of the composite material.

[0188] The composite materials and preparation methods thereof, optoelectronic devices and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a composite material, characterized in that: The steps include: Providing a precursor solution, wherein the precursor solution includes Mxene, a metal cation source and a first solvent; Hydrothermal treatment to obtain an inorganic semiconductor particle / Mxene composite material solution; The inorganic semiconductor particle / Mxene composite material solution is subjected to microwave treatment to obtain a composite material, wherein the composite material comprises inorganic semiconductor particles and Mxene quantum dots.

2. The preparation method according to claim 1, characterized in that The power of the microwave treatment is 550-570 W, and the time is 3-5 min; and / or. The temperature of the hydrothermal treatment is 170-200° C., and the time is 30 min-1 h.

3. The preparation method according to claim 1, characterized in that: In the precursor solution, the concentration of Mxene is in the range of 0.6 to 1 mg / mL; and / or The concentration range of the metal cation source is 0.01 to 0.1 mmol / mL; and / or In the inorganic semiconductor particle / Mxene composite material solution, the concentration of the inorganic semiconductor particle / Mxene composite material is 20-100 mg / ml.

4. The preparation method according to claim 1, characterized in that: The chemical general formula of the Mxene is M n+1 X n T x , where M is selected from transition metal elements, and the transition metal elements are selected from one or more of Ti, Nb, V, Mo, Zr, Hf, Ta, Cr, and Sc; X is selected from one or more of C and N; T x is a surface active functional group, including one or more of -OH, -O, -F, -Cl, and -Br, where 0 < x ≤ 2; n is any integer among 1, 2, and 3; and / or The first solvent includes an alcohol solvent, and the alcohol solvent includes but is not limited to one or more of ethylene glycol, diethylene glycol, 2-propylene glycol, 1,4-butanediol, and 1,6-hexanediol; and / or The inorganic semiconductor particle / Mxene composite material comprises Mxene nanosheets and inorganic semiconductor particles loaded on the surface of the Mxene nanosheets.

5. The preparation method according to claim 1, characterized in that: The Mxene includes Ti3C2T x 、Ti2CT x 、TiNbCT x 、Ti3CNT x 、Ta4C3T x 、Nb2CT x 、Nb4C3T x 、V2CT x 、Mo2CT x and Ti4N3T x One or more of, where 0 <x≤2。 6. The preparation method according to claim 1, characterized in that: The metal cation source includes one or more of a zinc source, a titanium source, a tin source, a zirconium source and a tantalum source.

7. The preparation method according to claim 6, characterized in that: The zinc source includes one or more of zinc acetate, zinc sulfate, zinc nitrate and zinc chloride; and / or The titanium source includes one or more of titanium acetate, titanium sulfate, titanium nitrate and titanium chloride; and / or The tin source includes one or more of tin acetate, tin sulfate, tin nitrate, and tin chloride; and / or The zirconium source includes one or more of zirconium acetate, zirconium sulfate, zirconium nitrate, and zirconium chloride; and / or The tantalum source includes one or more of tantalum acetate, tantalum sulfate, tantalum nitrate, and tantalum chloride.

8. The preparation method according to claim 1 or 6, characterized in that: A doping element source is also added to the precursor solution, and the doping element source includes one or more of magnesium salts, lithium salts, manganese salts, yttrium salts, lanthanum salts, copper salts, nickel salts, zirconium salts, cerium salts, indium salts, gallium salts and tin salts.

9. The preparation method according to claim 8, characterized in that: The molar ratio of the doping element source to the metal cation source is greater than 0 and less than or equal to 0.3:

1.

10. A composite material, characterized in that: The composite material comprises inorganic semiconductor particles and Mxene quantum dots, wherein the inorganic semiconductor particles are doped in the Mxene quantum dots.

11. The composite material according to claim 10, characterized in that The chemical general formula of the Mxene is M n+1 X n T x , where M is selected from transition metal elements, and the transition metal elements are selected from one or more of Ti, Nb, V, Mo, Zr, Hf, Ta, Cr, and Sc; X is selected from one or more of C and N; T x is a surface active functional group, including one or more of -OH, -O, -F, -Cl, and -Br, where 0 < x ≤ 2; n is any integer among 1, 2, and 3; and / or The inorganic semiconductor particles include one or more of doped metal oxide particles and undoped metal oxide particles, the metal oxide in the doped metal oxide and the metal oxide in the undoped metal oxide particles each independently include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and the doping element in the doped metal oxide includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, Sn; and / or The average particle size of the inorganic semiconductor particles is 50 to 200 nm; and / or In the composite material, the mass ratio of the inorganic semiconductor particles to the Mxene quantum dots is in the range of 30% to 60%.

12. A photoelectric device, comprising a first electrode and a second electrode arranged opposite to each other, and further comprising an electron transport layer located between the first electrode and the second electrode, characterized in that: The material of the electron transport layer includes the composite material prepared by the preparation method according to any one of claims 1 to 9, or includes the composite material according to any one of claims 10 to 11.

13. The optoelectronic device according to claim 12, characterized in that The first electrode and the second electrode independently include a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium doped tin oxide, fluorine doped tin oxide, antimony doped tin oxide, aluminum doped zinc oxide, gallium doped zinc oxide, indium doped zinc oxide, magnesium doped zinc oxide and aluminum doped magnesium oxide, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or The optoelectronic device further includes a light-emitting layer, which is located between the first electrode and the electron transport layer or between the second electrode and the electron transport layer. The material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material. The organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing BN covalent bonds, hybrid localized charge transfer excited state materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn STe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, One or more of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlN As, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, and the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2 + 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; and / or The photoelectric device further comprises a hole transport layer located on a side of the light-emitting layer away from the electron transport layer, wherein the hole transport layer comprises a material comprising 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'- Bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl- 4-4'-diamine, spiro NPB, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 1,3-bis(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary One or more of amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylates and their derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or The photoelectric device also includes a hole injection layer located on a side of the light-emitting layer away from the electron transport layer, and the material of the hole injection layer includes one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

14. A display device, characterized in that: The optoelectronic device comprises the optoelectronic device according to any one of claims 12 to 13.

Citation Information

Cited By

  • 3D printing nanometer microbattery composite electrode material and preparation method thereof

    CN120497325A